2013
DOI: 10.1111/1440-1681.12162
|View full text |Cite
|
Sign up to set email alerts
|

Fructose, pregnancy and later life impacts

Abstract: Fructose is an increasingly common constituent of the Westernized diet due to cost and production efficiencies. Although an integral component of our pre-industrial revolution diet, over the past two decades human and animal studies have highlighted that excessive fructose intake appears to be associated with adverse metabolic effects. Excessive intake of fructose is the combined result of increased total energy consumption and increased portion sizes of foods, which often incorporate the fructose-containing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 153 publications
(219 reference statements)
5
63
0
Order By: Relevance
“…The problem is certainly a deep concern in Mexicans and Mexican-Americans for whom socioeconomic disadvantage, race/ethnic disparities and genetics play a key role in overweight and obesity status (Bonvecchio et al, 2009;Piernas et al, 2014;Fowler et al, 2013;Rossen, 2014;Bauer et al, 2014). Compounding the problem in Mexican children is their current high fructose consumption: Mexico is the world's biggest per capita consumer of soft drinks and the change from cane sugar to high fructose corn syrup will aggravate obesity, chronic metabolic disease, cognitive decline and increase the risk of Alzheimer's disease (Lakhan and Kirchgessner, 2013;Lustig, 2013;Regnault et al, 2013;Sloboda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is certainly a deep concern in Mexicans and Mexican-Americans for whom socioeconomic disadvantage, race/ethnic disparities and genetics play a key role in overweight and obesity status (Bonvecchio et al, 2009;Piernas et al, 2014;Fowler et al, 2013;Rossen, 2014;Bauer et al, 2014). Compounding the problem in Mexican children is their current high fructose consumption: Mexico is the world's biggest per capita consumer of soft drinks and the change from cane sugar to high fructose corn syrup will aggravate obesity, chronic metabolic disease, cognitive decline and increase the risk of Alzheimer's disease (Lakhan and Kirchgessner, 2013;Lustig, 2013;Regnault et al, 2013;Sloboda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Effective January 2014, a significant increment in the cost of soft drinks by the 8% federal tax, resulted in the substitution of sugar cane by high-fructose corn syrup (HFCS) by the soft drink industry in Mexico. An increase in HFCS will severely aggravate the obesity, chronic metabolic disease, cognitive decline and risk of Alzheimer's disease in exposed children (Lakhan and Kirchgessner, 2013;Lustig, 2013;Regnault et al, 2013;Sloboda et al, 2014). The complexity of the systemic inflammation, neuroinflammation and the early hallmarks of AD in Mexico City teens is worsen by data supporting that adipokines mediate inflammation and insulin resistance (Kwon and Pessin,2013) and deficient brain insulin signaling pathways are critical etiological factors in Alzheimer's disease De la Monte, 2014).…”
mentioning
confidence: 99%
“…Thus far, only a limited number of human studies have shown an association between excessive sweetened food and beverage consumption and poor pregnancy outcome [24]. Animal studies have shown that fructose alone alters fetal and offspring metabolism [24]. However, several animal studies have often used fructose as a part of diet along with sucrose, fat, and salt.…”
Section: Effect Of Maternal Fructose Consumption On Programmed Hypmentioning
confidence: 99%
“…This increased nutrient supply appears to be due to the combined effects of the tendency of overweight/obese women to consume diets that contain greater amounts of noncore foods [13] and the fact that these women also tend to be more insulin resistant than their lean counterparts (FIGURE 1) [2]. A number of dietary factors have been implicated in metabolic programming, including higher intakes of total energy, saturated and omega-6 fats, refined/high-glycemic index (GI) carbohydrates, fructose and sucrose, and reduced intakes of key micronutrients [13][14][15][16]. Thus far, however, which of these nutritional factors are the key drivers of metabolic programming remains unclear.…”
Section: Maternal Obesity and Nutrient Supply To The Developing Fetusmentioning
confidence: 99%